Perspectives on Differentiation: Negotiating Traditional Knowledge on the International Level - Stefan Groth (Journal of Ethnology and Folkloristics, 2011)
This article explores different perspectives on indigenous communities and their traditional knowledge on the national level as well as on the global stage. It aims to provide a survey of such perspectives and the links and interdependencies between them using the example of the world Intellectual Property organization’s Intergovernmental Committee on Intellectual Property and Genetic Resources, Traditional Knowledge and Folklore (WIPO’s IGC). It is argued that different socio-political constellations and power relations lead to terminological perspectives of differentiation, i.e. the semantic construction of an external Other in the past that is used to evaluate the present and place oneself in a position of advantage.